Students’ Cognition and Attitude in Writing Descriptive Text - Indah Sari; Anni Holila Pulungan; Rahmad Husein (Britain International for Academic Research (BIAR) Publisher, 2020)
College students are in formal operational in period of cognitive development which they can use symbols logically related to abstract concepts, acquire flexibility in thinking as well as the capacities for abstract thinking and mental hypothesis and consider possible alternatives reasoning and problem solving. However, the students’ writings have some mistakes in terms of using surface features such as spelling, grammar, usage, punctuation, grammar, vocabulary and tenses. This study aimed to analyze about the students’ cognition and attitude in writing descriptive text. The design of this study was descriptive qualitative by conducting the in-depth interview and questionnaire administration. The data of this study were the sentences in descriptive text and transcript of interview. Moreover, the data source were 2 students of 7th semester at STBA – PIA Medan. The results showed that 1) the dominant type of students’ attitude in writing descriptive text was cognitive domain followed by affective and conative domains which could be interpreted that the students had positive attitude regarding to the writing of descriptive text, 2) the students’ cognition in writing descriptive text was having the stages of writing process which consists of pre-writing, drafting, revising, editing and publishing, and 3) the reasons of applying the students’ cognition and attitude in descriptive text were they had the goals and purposes in their thoughts when they were writing. Moreover, they believed that writing could improve their skills in learning English as a foreign language.